2022
DOI: 10.21037/atm-22-2382
|View full text |Cite
|
Sign up to set email alerts
|

Midkine promotes kidney injury in diabetic kidney disease by increasing neutrophil extracellular traps formation

Abstract: Background: We sought to investigate the role of midkine (MK) on neutrophil extracellular trap formation (NETosis) and diabetic kidney disease (DKD) progression. Methods: The expression of MK and NETosis in the renal tissue of DKD patients was examined by immunohistochemistry and immunofluorescence, respectively. Neutrophils extracted from mouse bone marrow by gradient centrifugation were treated with MK for this in-vitro study. A mouse diabetes model was induced by a high-fat diet combined with an intraperito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Prior studies have demonstrated that depleting or inhibiting neutrophils can protect against pancreatic tissue damage in inflammatory responses reliant on neutrophil activity ( Cui et al, 2017 ). Neutrophil-induced NETosis is a distinct form of neutrophil death that differs from apoptosis and necrosis and significantly contributes to tissue damage ( Liu et al, 2022 ; Wang C. L. et al, 2023 ). By responding to chemokines, activated neutrophils migrate into the site of inflammation, produce antimicrobial agents, and undergo NETosis ( Balachandran et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated that depleting or inhibiting neutrophils can protect against pancreatic tissue damage in inflammatory responses reliant on neutrophil activity ( Cui et al, 2017 ). Neutrophil-induced NETosis is a distinct form of neutrophil death that differs from apoptosis and necrosis and significantly contributes to tissue damage ( Liu et al, 2022 ; Wang C. L. et al, 2023 ). By responding to chemokines, activated neutrophils migrate into the site of inflammation, produce antimicrobial agents, and undergo NETosis ( Balachandran et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In several inflammatory diseases, MK has been shown to exacerbate the condition through promoting NETosis, neutrophil trafficking, and macrophage accumulation [43,44,127,128]. Based on the findings discussed in the preceding section, it is reasonable to suggest that accelerated MK expression contributes to the recruitment of innate immune cells, which helps to modulate the immunopathology in COVID-19 patients.…”
Section: Intercellular Communication Of Mk In Covid-19mentioning
confidence: 92%
“…Strong MDK expression was observed in patients with diabetic nephropathy 17 and other inflammatory conditions 18 , 19 . Liu et al reported that promoted expression of MDK accelerated the pathological damage and fibrosis in diabetic kidney diseases by increasing neutrophil extracellular trap 20 . Similarly, Misa et al found knockout of Mdk significantly ameliorated lung fibrosis with lower expression of both collagen and α-Smooth Muscle Actin (ACTA2) 21 .…”
Section: Introductionmentioning
confidence: 99%